Evaluasi Pengaruh Jumlah dan Posisi Stasiun Curah Hujan pada Simulasi Aliran Limpasan Di Sungai Ping, Thailand - Muchamad Wahyu Trinugroho (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
The number and distribution of rainfall stations areneeded to simulate rainfall-run off transformation on hydrologic model. However, the availability of stations varies in watershed. The study aims to assess theinfluence of numberand distribution rainfall stations by a modelling approachto simulate run-off process. The use of HEC-HMS model is tocalibrate model parameters and simulaterun-offon 4 scenarios in Mae Caem Watershed (3,826 km2), Northern Thailand. The result shows the calibrated model parameters of 13 stationsare very satisfied by 0.826 of Nash coefficient. Based on the simulation result, the condition of 6 stations demonstrate the best fit regarding observation data by R2 = 0.927; the lowest correlation is three rainfall stations by 0.795 of R2. Also, simulated runoff rainfall for six stations (condition2) show results close to the observation discharge. Condition 1 (all stations) is somewhat higher than condition tworegarding pattern and peak discharge. Another result shows simulation of peak discharge condition 3 (station number 2, 5, and 13) has overestimate of observation discharge and condition 5 shows underestimate result to observation discharge. Overall the simulation results have met Nash's criteria, while the best results are in simulation with 6 stations (condition 2). Thus the number and position of rainfall stations have an influence on the modeling of rainfall runoff in the Ping River, Mae Caem Watershed.